Solar selective coatings - Yianoulis, Panayiotis; Giannouli, Myrsini; Kalogirou, Soteris A.; Yianoulis, Panayiotis (My University, 2012)
Solar selective coatings are used on photothermal absorbers of solar systems. They enhance the efficiency of photothermal conversion, especially at elevated temperatures, by the reduction of thermal radiation losses. The spectral selectivity of the absorber is determined by its high 'absorptance'.a in the short-wavelength region of the solar radiation of about 0.3-3. mm and low 'emittance' e at the far-infrared region of the spectrum corresponding to the blackbody thermal emittance at the operating temperature of the absorber. Typical values for these properties of selective surfaces are 0.90 for absorptance and 0.10 for the emittance. 'Selectivity' is defined as the ratioa/ε.
Keywords: Interference stacks; Metal particles in a ceramic matrix; Photothermal conversion; Selective absorbing surfaces; Selective coatings; Solar energy conversion; Solar energy selective absorbers; Solar selective coatings; Spectrally selective coatings; Tandem stacks